2022
DOI: 10.1111/age.13181
|View full text |Cite
|
Sign up to set email alerts
|

The de novo assembly of a European wild boar genome revealed unique patterns of chromosomal structural variations and segmental duplications

Abstract: The rapid progress of sequencing technology has greatly facilitated the de novo genome assembly of pig breeds. However, the assembly of the wild boar genome is still lacking, hampering our understanding of chromosomal and genomic evolution during domestication from wild boars into domestic pigs. Here, we sequenced and de novo assembled a European wild boar genome (ASM2165605v1) using the long‐range information provided by 10× Linked‐Reads sequencing. We achieved a high‐quality assembly with contig N50 of 26.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…When focusing on the long SVs over 1000bp, we found that X chromosome was the most extreme outlier of the linear pattern that shapes autosomes (Figure 1D, p < 0.001). This pattern indicates the “faster-X divergence” in principle [63], which is consistent with a previous observation in other mammalian species based on segmental duplication identified using only SyRI [27].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…When focusing on the long SVs over 1000bp, we found that X chromosome was the most extreme outlier of the linear pattern that shapes autosomes (Figure 1D, p < 0.001). This pattern indicates the “faster-X divergence” in principle [63], which is consistent with a previous observation in other mammalian species based on segmental duplication identified using only SyRI [27].…”
Section: Resultssupporting
confidence: 91%
“…which is consistent with a previous observation in other mammalian species based on segmental duplication identified using only SyRI [27].…”
Section: Excess Number Of Svs Was Found In X Chromosomesupporting
confidence: 93%
See 1 more Smart Citation
“…Although the “assembly-to-assembly” approach has been successfully used to identify SVs in other species ( Chen et al, 2022b ; Goel et al, 2019 ), we failed to obtain results from this method, probably due to the known phenomenon of higher rearrangements in plants than in animals. We further identified structural variations (SVs) using Sniffles V2.0.3 ( Sedlazeck et al, 2018 ) and a dual-alignment strategy implemented in Vulcan ( Fu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 86%
“…We first used reference sequences of six suids for genome alignment: the domestic Duroc (Sscrofa11.1) and Diannan small‐ear pig, the European wild boar (also belonging to S. scrofa ), Visayan warty pig ( Sus cebifrons ), and the African common warthog and red river hog (Chen et al, 2022; Liu et al, 2022; Warr et al, 2020; Xie et al, 2022). Cattle (Rosen et al, 2020) and horse (Kalbfleisch et al, 2018) served as outgroups (Appendix S1).…”
Section: Figurementioning
confidence: 99%